2014
DOI: 10.1371/journal.pone.0098582
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CD26 in Patients with Colorectal Cancer

Abstract: BackgroundCD26, dipeptidyl peptidase IV, was discovered firstly as a membrane-associated peptidase on the surface of leukocyte. We previously demonstrated that a subpopulation of CD26+ cells were associated with the development of distant metastasis, enhanced invasiveness and chemoresistance in colorectal cancer (CRC). In order to understand the clinical impact of CD26, the expression was investigated in CRC patient's specimens. This study investigated the prognostic significance of tumour CD26 expression in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 32 publications
6
49
0
1
Order By: Relevance
“…We have also shown that CD26+ correlates with the clinical stage on immunohistochemistry [4]. This study shows that confirmed or suspected stage IV primary tumors have a relatively large CD26+ subpopulation, while in stage I to III disease there is no apparent trend of the CD26+ population increasing with the increase of the disease stage.…”
Section: Discussionsupporting
confidence: 54%
“…We have also shown that CD26+ correlates with the clinical stage on immunohistochemistry [4]. This study shows that confirmed or suspected stage IV primary tumors have a relatively large CD26+ subpopulation, while in stage I to III disease there is no apparent trend of the CD26+ population increasing with the increase of the disease stage.…”
Section: Discussionsupporting
confidence: 54%
“…Beyond diabetes, the role of DPP4 has been widely studied in several types of cancer, including CRC. The expression of DPP4 correlated with the populations of cancer stem cells and poor survival in human CRC (Lam et al, 2014;Pang et al, 2010). DPP4 has peptidase activity and is able to cleave and degrade many biologically active peptides (Tanaka et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Our current data also support an emerging anticancer strategy and suggest that pharmacological induction of ferroptosis may be effective in genotype-selected subgroups of CRC patients. In particular, the presence of two genotypes associated with poor prognosis in CRC-namely, TP53 mutation/ deletion (Fearon, 2011) combined with DPP4 overexpression (Lam et al, 2014) -is likely to characterize a target population that would profit from treatment with erastin and perhaps other yet-to-be-developed ferroptosis inducers. Identification and characterization of unknown nuclear localization signals in DPP4 could be important in understanding the locationdependent role of DPP4 in ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is variability between various forms of cancers regarding the efficacy of DPP4 (8). DPP4 is upregulated in many aggressive types of T-cell malignancies (9), esophageal adenocarcinoma (10), lung adenocarcinoma (11), thyroid carcinoma (12), and prostate cancer (13), and a high level of DPP4 is indicative of poor prognosis for papillary thyroid carcinoma (14), urothelial carcinoma (15), and colorectal cancer (16). In contrast, DPP4 is downregulated in tissues of liver cirrhosis (17), endometrial adenocarcinoma tissues (18), and a low serum level of DPP4 was related to a poor prognosis for patients who have esophageal squamous cell carcinoma (19).…”
Section: Introductionmentioning
confidence: 99%